Aphids on Landscape Plants - Eileen A. Buss (EDIS)
Revised! ENY-320, a 4-page illustrated fact sheet by E.A. Buss describing these common landscape pests, what insects prey on them, how to inspect plants for the presence of aphids, and how to control them with and without using insecticides. This version is updated to include a new table listing insecticides labeled for use by homeowners against aphids in Florida, in addition to the listing of those registered for professional use. Part of the Master Gardener Handbook. Originally published by the UF Entomology and Nematology Department, October 1993. Revised June 2006.